Material issues in additive manufacturing: A review. (January 2017) - Singh, Sunpreet; Ramakrishna, Seeram; Singh, Rupinder
Abstract: Today, Additive manufacturing (AM) is a well known technology for making real three dimensional object, with metal or ceramic or plastic or thereby combination, which may be subjected to various applications. Additive bio-manufacturing (ABM) techniques are highly in demand and researches have been going on for making these safer and more versatile. For more utilization and versatility, special attention is required to develop new materials which can help in increasing the service life, bioactivity, cell growth along with the desired mechanical properties. The present paper aims to review some of the most widely used AM techniques for biomedical applications. Special attention has been paid on Fused deposition modeling (FDM) based AM technique as it is economical, environmentally friendly and adaptable to flexible filament material. This review paper will be helpful to the researchers, scientists, manufacturers, etc., working in the field of ABM.